2008
DOI: 10.1103/physrevd.78.063528
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic vacuum variable and equilibrium approach in cosmology

Abstract: A modified-gravity theory is considered with a four-form field strength F , a variable gravitational coupling parameter G(F ), and a standard matter action. This theory provides a concrete realization of the general vacuum variable q as the four-form amplitude F and allows for a study of its dynamics. The theory gives a flat Friedmann-Robertson-Walker universe with rapid oscillations of the effective vacuum energy density (cosmological "constant"), whose amplitude drops to zero asymptotically. Extrapolating to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
205
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(211 citation statements)
references
References 30 publications
6
205
0
Order By: Relevance
“…(5.16) of Ref. [7] (and reiterated in the review [10]), the present value of this quantity ½Ã þðt now Þ would be of the order of the experimental value à ðexpÞ $ ðmeVÞ 4 .…”
Section: Numerical Solutionsmentioning
confidence: 87%
See 1 more Smart Citation
“…(5.16) of Ref. [7] (and reiterated in the review [10]), the present value of this quantity ½Ã þðt now Þ would be of the order of the experimental value à ðexpÞ $ ðmeVÞ 4 .…”
Section: Numerical Solutionsmentioning
confidence: 87%
“…Inspiration for this model was obtained from previous work by Volovik and one of the present authors on the so-called q-theory approach [6][7][8][9] to the main cosmological constant problem (a one-page review of q-theory can be found in Appendix A of Ref. [10] and a ultrabrief summary will be given in the Footnote of Sec.…”
Section: Introductionmentioning
confidence: 97%
“…However, it is remarkable that it matches its order of magnitude, (at least for the current epoch), albeit any dynamical model implementing this idea will probably have to do so only at late times to avoid possible tension with the observational data. Guided by these lessons, there are already a number of heuristic investigations about how a cosmological term could dynamically adapt to the evolution of the matter content, and which implications it could have for the evolution of the universe [27, 350, 349, 351]. …”
Section: Towards a Theory Of Quantum Gravity?mentioning
confidence: 99%
“…This numerical coincidence is impressive and also means that this model gets rid of fine tuning problem [8,9]. Actually, several authors have already suggested DE model with energy density proportional to Λ 3 QCD H in different physical contexts [15,16,17,18,19,20,21,39, 40] such as QCD trace anomaly, gluon condensate of quantum chromodynamics, modifying gravity and so on.…”
Section: Introductionmentioning
confidence: 97%